The haptoglobin 2-2 genotype is associated with a reduced incidence of Plasmodium falciparum malaria in children on the coast of Kenya - Atkinson, S; Mwangi, T; Uyoga, S; Ogada, E; Marsh, K; Prentice, A; Williams, T (University of Chicago Press, 2007)
Background: Haptoglobin (Hp) genotype determines the efficiency of haemoglobin clearance after malaria-induced hemolysis and alters antioxidant and immune functions. The Hp² allele is thought to have spread under strong selection pressure, but it is unclear whether this is due to protection from malaria or other diseases. Methods: We monitored the incidence of febrile malaria and other childhood illnesses with regard to Hp genotypes in a prospective cohort of 312 Kenyan children during 558.3 child-years of follow-up. We also conducted 7 cross-sectional surveys to determine the prevalence of Plasmodium falciparum parasitemia. Results: The Hp ^2/2 genotype was associated with a 30% reduction in clincal malarial episodes (adjusted incidence rate ratio, 0.67; P = .008 for Hp^ 2/2 vs. Hp ^1/1 and Hp ^2/1 combined). Protection increased with age; there was no protection in the first 2 years of life, 30% protection at ≥2 years of age, and 50% protection from 4-10 years of age. Children with the Hp ^1/1 genotype had a significantly lower rate of nonmalarial fever (P= .001). Conclusions: Balancing selection pressures may have influenced the spread of the Hp gene. Our observations suggest that the Hp² allele may have spread as a result of protection from malaria, and the Hp¹ allele may be sustained by protection from other infections.